PENGEMBANGAN APLIKASI MOSAIK BANGSA UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI KEBERAGAMAN SUKU BANGSA KELAS IV - Siti Nur Hayati Meidi; Kusman Rukmana; Sidqia Nurfadilah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research is motivated by the low learning outcomes of students on the subject of ethnic diversity and the less than optimal use of technology-based learning media in PPKn learning in elementary schools. This study aims to develop an Android-based MOSAIK BANGSA application and determine the feasibility and effectiveness of its use in improving the learning outcomes of fourth-grade students. The research method used is Research and Development (R&D) with the ADDIE development model which includes the stages of analysis, design, development, implementation, and evaluation. The subjects of this study were 28 fourth-grade students of SDN Citimun 1. The instruments used included validation sheets from material experts and media experts, learning outcome tests in the form of pretests and posttests, student response questionnaires, and student activity observation sheets. The results showed that the MOSAIK BANGSA application was declared very feasible to use with a percentage of validation from material experts of 87.5%. The results of the application implementation showed an increase in student learning outcomes, namely the average pretest score of 52.00 increased to 80.33 in the posttest with an N-gain value of 0.6013 which is included in the moderate category. Furthermore, student response to the application's use reached 90.6%, and student activity during learning reached 92.5%, categorized as very good. Based on these results, it can be concluded that the MOSAIK BANGSA application is effective as an interactive and innovative learning medium to improve student learning outcomes in the subject of ethnic diversity in grade IV elementary schools.